INISIATIF SEKOLAH RAMAH ANAK: UPAYA PREVENTIF TERHADAP PUTUS SEKOLAH DAN PERUNDUNGAN DI SMP - Khotibul Umam; Nabillah Mufidzah; Ina Mutmainah (Unperba Press, 2026)
This study aims to increase public awareness, especially among students, about the dangers and impacts of perundungan, prevent perundunganin the school environment, encourage victims of perundunganto dare to report the incidents they experience and create a safe, comfortable and inclusive school and community environment for all. This socialization program involves various activities, such as counseling on the importance of education, the negative impacts of perundungan, and life skills needed by students. In addition, discussion group activities, quizzes on the material presented, role-playing and penghargaan giving are also carried out to improve students' understanding of the material presented. This study used quantitative and qualitative methods involving students, teachers, and parents as subjects of community service. Quantitative data were obtained through questionnaires, while qualitative data were obtained through in-depth interviews. The results of the community service showed that the socialization program implemented was quite effective in increasing students' awareness of the importance of education and the negative impacts of perundungan. Most students stated that they understood more about the problems of dropping out of school and perundunganafter participating in this program. In addition, this program also succeeded in creating a more positive and inclusive school environment. However, there are still several obstacles that need to be considered, such as the lack of parental involvement in this program and the fact that some students still find it difficult to change their perundunganbehavior. Therefore, ongoing efforts need to be made to overcome these obstacles. As a recommendation, it is necessary to conduct periodic evaluations of this socialization program to see its progress. In addition, it is necessary to involve all stakeholders, including parents, teachers, and the community, in efforts to prevent dropping out of school and overcome perundungan.